Fabrication of Electrochemically Reduced Graphene Oxide Modified Gas Diffusion Electrode for In-situ Electrochemical Advanced Oxidation Process under Mild Conditions. (20th December 2016) - Dong, Heng; Su, Huimin; Chen, Ze; Yu, Han; Yu, Hongbing
Graphical abstract: Abstract: With aim to develop an efficient heterogeneous metal-free cathodic electrochemical advance oxidation process (CEAOP) for persistent organic pollutants (POPs) removal from wastewater under mild conditions, electrochemically reduced graphene oxide (ERGO)-modified gas diffusion electrode (GDE) was prepared for oxygen-containing radicals production via electrochemical oxygen reduction reaction (ORR). A detailed physical characterization was carried out by SEM, Raman spectroscopy, XRD and XPS. The electrocatalytic behavior for ORR was investigated by electrochemical measurements and electrolysis experiments under constant current density. Bisphenol A (BPA) of 20 mg L −1 was used as a model of POPs to evaluate the performance of the CEAOP with ERGO-modified GDE. The results showed that the defects concentration and electrochemical active sites of the ERGO was increased as the reduction time (30 min, 60 min and 120 min), leading to different catalysis on ORR. O2 generation via one-electron ORR was found under the electrocatalysis of ERGO (60 min and 120 min), contributing to a complete degradation of BPA within 20 min and a mineralization current efficiency (MCE) of 74.60%. An alternative metal-free CEAOP independent of Fenton reaction was established based on ERGO-modified GDE for POPs removal from wastewater under mild conditions.